Factors Impacting the Design of Innovative WIL Education - O'Rourke, Mark; Vesty, Gillian; Magdziarz, Sonia; Mudalige, Priyantha; Vitale, Connie; Bowyer, Dorothea; Nair, Sujay; Soltys, Sharon (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
The issues and experiences of work-integrated learning (WIL) accounting and financial planning academics across higher education (HE) institutions in developing innovative WIL programs are discussed by the authors. The authors reflect on their responsibilities and goals and how these aligned with student and institutional expectations for both work-based situations as well as classroom-based simulations. Cross-institutional collaboration on WIL approaches in undergraduate and postgraduate accounting courses reveal contrasting priorities and tensions when addressing the needs of stakeholders. Particularly noticeable are the institutional requirements for a technology-driven WIL curriculum, that meet with student, industry and institutional expectations. We contribute with insights on educator preparedness for delivering technology enhanced WIL programs and provide an in-depth analysis of academic engagement with WIL designs. Drawing on Activity Theory to analyse the constraints and confluences perceived in the design and teaching of WIL programs, this research contributes to our understanding of effective ways to manage this activity.